Azoxystrobin dissipation and its effect on soil microbial community structure and function in the presence of chlorothalonil, chlortetracycline and ciprofloxacin. (February 2020) - Han, Lingxi; Liu, Yalei; Fang, Kuan; Zhang, Xiaolian; Liu, Tong; Wang, Fenglong; Wang, Xiuguo
Abstract: The residual characteristics and the adsorption-desorption behaviors of azoxystrobin (AZO) as well as the soil ecological effects in the individual repeated treatments of AZO and its combination with chlorothalonil (CTL), chlortetracycline (CTC) and ciprofloxacin (CIP) were systematically studied in organic manure (OM)-amended soil under laboratory conditions. The presence of CTL, CTC, and CIP, both individually and combined, decreased the sorption affinity of AZO with the Freundlich adsorption and desorption coefficient decreasing by 0.3–24.2%, and CTC and CIP exhibited greater adverse effects than CTL. AZO dissipated slowly and the residues significantly accumulated during ten repeated treatments. The dissipation of AZO was inhibited to different degrees in the combined treatments. Biolog analysis revealed that the soil microbial functional diversity in the OM-soil + AZO and OM-soil + AZO + CTL treatments was higher than that in the OM-soil treatment during the former three repeated treatments, but which was inhibited during the latter seven repeated treatments. The soil microbial functional diversity in the OM-soil + AZO + CTC, OM-soil + AZO + CIP and OM-soil + AZO + CTL + CTC + CIP treatments was inhibited during the ten repeated treatments compared with OM-soil treatment. Metagenomic results showed that all repeated treatments significantly increased the relative abundance of Actinobacteria, but significantly decreased that of Proteobacteria and Firmicutes during the ten repeated treatments. Furthermore, the relative abundance of soil dominant bacterial genera Rhodococcus, Mycobacterium and Arthrobacter in all the repeated treatments significantly increased by 1.5–1283.9% compared with the OM-soil treatment. It is concluded that coexistence of CTL, CTC and CIP, both individually and combined, with AZO can inhibit the dissipation of AZO, reduce the adsorption affinity of AZO on soil, and alter the soil microbial community structure and functional diversity. Graphical abstract: Image 1 Highlights: CTL, CTC and CIP decreased the adsorption affinity of AZO in soil. Repeated treatments decreased the degradation of AZO. CTL, CTC and CIP inhibited the degradation of AZO during ten repeated treatments. Repeated treatments altered soil microbial functional diversity. Repeated treatments changed soil microbial community structure. Abstract : Combined repeated treatments with AZO, CTL, CTC and CIP decelerated the AZO dissipation and changed the soil microbial community structure and functional diversity.